The Influence of Learning Media on the Quality of Progress Office Administration Program - Suciati Suciati; Kholid Kholid; Riesca Anindya Septantina (Journal of Managerial Sciences and Studies, 2024)
This research aims to describe the use of learning media and the quality of learning in the Office Administration Skills program at Watampone State Vocational School 1 as well as the influence of learning media on the quality of the teaching and learning process there. This research uses experimental research with a population of 208 students there, with a sample of 68 students with an error rate of 10 percent. Data collection was carried out using observation and questionnaires. The data analysis techniques used are descriptive statistics and inferential statistics. The results of this research show that the use of learning media there is classified as good from the aspects of print media, electronic media and reality media. The quality of the teaching and learning process there is assessed as good in terms of active, innovative, creative, effective and enjoyable learning. There is a significant positive influence of the use of learning media on the quality of learning in the office administration skills program at SMK Negeri 1 Watampone, amounting to 17.9 percent.